Jupiter: a toolkit for interactive large model visualization - Bartz, D.; Staneker, D.; Strasser, W.; Cripe, B.; Gaskins, T.; Orton, K. (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
The fast increasing size of datasets in scientific computing, mechanical engineering, or virtual medicine is quickly exceeding the graphics capabilities of modern computers. Toolkits for the large model visualization address this problem by combining efficient geometric techniques, such as occlusion and visibility culling, mesh reduction, and efficient rendering. We introduce Jupiter, a toolkit for the interactive visualization of large models which exploits the above mentioned techniques. Jupiter was originally developed by Hewlett-Packard and EAI, and it has been equipped with new functionality by the University of Tubingen, as being part, of the Kelvin project. An initial version of Jupiter has been released as open source.